200 Architects in the 1870s? Is that figure real? - Humphris, Adrian; Mew, Geoff (Architectural History Aotearoa, 2018)
In this paper we are using our architects dataset to identify every person who called themself an architect in New Zealand in the 1870s. An initial check of our database produced around 200 names, but we know from our previous studies that this figure needs to be refined to gauge the importance of their work, or even determine whether some of them could be truly called architects. We have taken our data and used key attributes to try to quantify and qualify our architects. For example, one initial crude sort was based on the numbers of buildings designed over their total careers; this should give some indication of their presumed competence and possible success in the profession. So-called architects who designed zero structures were assigned to the lowest class; other classes were; 1-5 structures; 6-20; and >21, the latter appearing to be the most successful. We also considered where each person was located for the bulk of the 1870s to see if there might be geographical trends related to their success or otherwise. To finish our analysis we have chosen a few architects as examples from each of our classes and described them in more detail to explain perceived trends.